Factors associated with the incidence of Hyperbilirubinemia in Neonates - Nurafni, Nurafni; Jawiah, Jawiah; Rohaya, Rohaya (Poltekkes Kemenkes Palembang, 2023)
Abstract Background: Hyperbilirubinemia defined as total serum bilirubin level≥5mg/ dL (86μmol/L). Hyperbilirubinemia is circumstances frequent transients _ found Good on baby Enough months (50-70%) as well baby premature (80-90%). Purpose: for know factors Which relate with incident hyperbilirubinemia on neonate in RSUP Dr. Rivai Abdullah Palembang year 2022. Method: research This is study descriptive approach quantitative , design cross sectional research . Population study Whole Treated neonates _ with hyperbilirubinemia in space neonates of RSUP Dr. Rivai Abdullah Palembang in 2022 totaling 102 respondents . Sample in study This done with technique non-random sampling in a manner total sampling as many as 102 respondents , Instrument research used _ record medical And checklist sheet . Analysis used _ is analysis univariate And bivariate . Test statistics used istest Chi Square . Results: chi square test obtained There is relationshiptype sex(p value = 0.03 <0.05), OR = 2.641, there is relationship age pregnancy (p-value = 0.007 <0.05), OR = 3.850, there is relationship breastfeeding (p value = 0.009 <0.05), OR = 0.038, There is no relationship infection (p value = 0.164 >0.05), OR = 2.421, There is no relationship hypoglycemia (p value = 0.633 >0.05), OR = 1.535 with incident hyperbilirubinemia Conclusion: There is relationship significant between type gender, age pregnancy and breastfeeding with incident hyperbilirubinemia, meanwhile infection And hypoglycemia There is no relationship significant with incident hyperbilirubinemia.